Analysis of Emotional Intelligence, Airmanship, and Situational Awareness Resilience to Indonesian Pilot Emergency Decision Making - Rizka Triansyah; Setyani Dwi Lestari (Business and Entrepreneurial Review, 2022)
Aircraft is a mean of transportation with the highest level of safety among other means of transportation, this is inseparable from improvements in the operating system, maintenance and improvement of rules in aviation safety and security. Among the causes of the plane crash, based on the recorded data, the HR factor or Human Error is the highest causal factor, and this cannot be separated from the Pilot's Decision Making in a flight. This study examines 3 aspects that must be considered by regulators and flight operators, including 1. Emotional Intelligence of an Aviator, 2. Airmanship and 3. Situational Awareness Resilience of a Pilot who has limitations on Emergency Decision Making Strategies. Sampling in this study used a random sampling technique with a total of 99 Indonesian Pilots. The data was collected using a questionnaire with a Likert scale which was processed using SPSS version 25. The research method used was multiple linear regression. The results of this study indicate that the Emotional Intelligence variable has a significant effect on emergency decision making, while the airmanship variable has no significant effect on emergency decision making, at the same time the situational awareness resilience variable has a significant effect on emergency decision making by Indonesian Pilots. The results of this study are expected to improve flight safety in Indonesia.